(untitled) (ART AND CULTURE BULLETIN, 2026)
his article provides a comprehensive analysis of the application of artificial intelligence technologies in national journalism, highlighting their main advantages and emerging challenges. The study examines the integration of artificial intelligence into the media sector of Uzbekistan, including news production, analytical content creation, automated text processing, and the development of visual materials. In addition, the article scientifically explores issues related to deepfake technologies, the spread of false content, the protection of personal data, and copyright regulations. The research also analyzes the ongoing reforms in Uzbekistan aimed at regulating artificial intelligence, while comparatively examining the experiences of China, the European Union, and Italy. The findings emphasize the importance of the responsible use of artificial intelligence in journalism, adherence to media ethics, the improvement of fact checking systems, and the strengthening of information security.